PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS DAN FINANCIAL LEVERAGE PADA BANK SYARIAH DI YOGYAKARTA - Chaidir Iswanaji (al-Uqud : Journal of Islamic Economics, 2018)
Sharia banks show a dynamic role in the economy in Yogyakarta. The purpose of this study is to see the impact Capital Structure on Profitability and Financial Leverage in syariah bank Yogyakarta. In this study data taken from Islamic banks in 2008-2016 from sixteen sharia banks. Data analysis used descriptive statistics, covariance analysis and regression model. The results of this study indicate that the capital structure has a significant effect on profitability and has no significant effect on financial leverage.